Effect of the indoor humidity control characteristics for amine grafted functionalized mesoporous silica nanomaterials. (2nd January 2023) - Lin, Ya-Wen; Lee, Wei-Hao; Kuo, Bo-Yi; Lin, Kae-Long
ABSTRACT: In this study, the silicon source and aluminum source rich in stone mud were extracted, and the best alkali fusion process for different alkali fusion temperatures and alkali agent ratios was determined by the alkali fusion salt method. The surface of the material was grafted by 3-aminopropyltriethoxysilane to obtain an amine grafted functionalized groups MCM-41 material (APTES/MCM-41). The APTES/MCM-41 material was analyzed and water adsorption/desorption experiment was performed. Utilizing stone sludge to obtain APTES/MCM-41, which has a high specific surface area (25.19 m 2 /g) and, an adjustable pore size and an easy structural surface grafted can use different functional groups for the development of new materials. The 24-h moisture adsorption capacity of the APTES/MCM-41 with 2.5 vol.% amine functional groups was 37.02 g/m 2, which conforms to JIS A 1470–1 specifications and far exceeds that of diatomaceous earth and inorganic materials in humidity control coatings (18.6 g/m 2 ). APTES/MCM-41 could be used as an alternative to mechanical dehumidifiers.